KEPASTIAN HUKUM PENGAKUAN PUTUSAN GANTI KERUGIAN LINGKUNGAN HIDUP SEBAGAI UTANG DALAM DAFTAR PIUTANG TETAP - Reza Kurnia Akbar; Dedi Harianto; Sunarmi Sunarmi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The implementation of the environmental damage compensation decision that has permanent legal force is not synchronized with the bankruptcy mechanism, where the state's claim for ecological restoration must compete with other creditors and is subject to strict procedures for matching receivables. The curator's rejection of the KLHK bill in the PT RKK case shows that the obligation for environmental compensation that is public and strategic is actually hampered by the formal time limit in the Bankruptcy Law and PKPU, thus raising questions about the effectiveness of environmental decisions as the basis for debt and the legal protection of the state as an environmental creditor in the bankruptcy process. With the research method used in this study, namely normative juridical, normative juridical research is "research where law is conceptualized as what is written in the legislation. The environmental compensation decision that has permanent legal force can be used as a legal basis for the emergence of debt in bankruptcy, so that the state is in the position of a concurrent creditor who has the right to be included in the Permanent Receivables List. Through the receivables verification mechanism and renvoi procedure, state legal protection is strengthened and the effectiveness of PMH decisions is guaranteed. Medan Commercial Court Decision No. 18/Pdt.Sus-Renvoi/2023 confirms this by stating that the obligation to compensate for environmental damages fulfills the elements of "debt" under the Bankruptcy and PKPU Laws, thus providing legal certainty and legitimacy for the state's rights in environmental restoration. Keywords: legal certainty, environment, compensation Abstrak: Tidak sinkronnya pelaksanaan putusan ganti rugi kerusakan lingkungan yang telah berkekuatan hukum tetap dengan mekanisme kepailitan, di mana klaim negara atas pemulihan ekologis harus bersaing dengan kreditor lain dan tunduk pada prosedur ketat pencocokan piutang. Penolakan kurator terhadap tagihan KLHK dalam kasus PT RKK menunjukkan bahwa kewajiban ganti rugi lingkungan yang bersifat publik dan strategis justru terhambat oleh batas waktu formal dalam UU Kepailitan dan PKPU, sehingga memunculkan pertanyaan mengenai efektivitas putusan lingkungan sebagai dasar utang serta perlindungan hukum negara sebagai kreditur lingkungan dalam proses kepailitan. Dengan metode penelitian yang digunakan pada penelitian ini yaitu yuridis normatif, penelitian yuridis normatif adalah â€œpenelitian dimana hukum dikonsepkan sebagai apa yang tertulis dalam peraturan perundang-undangan Putusan ganti kerugian lingkungan hidup yang telah berkekuatan hukum tetap dapat dijadikan dasar sah timbulnya utang dalam kepailitan, sehingga negara berkedudukan sebagai kreditur konkuren yang berhak dicantumkan dalam Daftar Piutang Tetap. Melalui mekanisme verifikasi piutang dan renvoi prosedur, perlindungan hukum negara diperkuat serta efektivitas putusan PMH tetap terjamin. Putusan Pengadilan Niaga Medan No. 18/Pdt.Sus-Renvoi/2023 menegaskan hal ini dengan menyatakan bahwa kewajiban ganti rugi lingkungan memenuhi unsur â€œutangâ€ menurut UU Kepailitan dan PKPU, sehingga memberikan kepastian dan legitimasi yuridis atas hak negara dalam pemulihan lingkungan. Kata kunci kepastian hukum , lingkungan hidup , ganti kerugian